The demonstration of reflection-in-action in maritime training. Issue 3 (4th May 2021) - Sellberg, Charlott; Lindwall, Oskar; Rystedt, Hans
ABSTRACT: The literature on simulation-based training highlights the importance of post-simulation debriefings as occasions for student self-reflection. Another central feature of these debriefings, which has not gained the same interest, is how debriefings are used by instructors to demonstrate professional modes of reflection-in-action: how they are used to show the deeply reasoned and skilled practices that characterize professional conduct. Based on video recordings of debriefing sessions in a navigation course for master mariners, this study discusses a case where an instructor demonstrates how navigational rules should be applied in line with good seamanship. With a starting point in the visual representation of the scenario, and by re-enacting the students' performance, the instructor formulates the problem that the students confronted in the scenario as well as potential solutions. In this way, the students' attempts to solve the task are explicated in terms of the more general lessons that the scenario was designed to teach. The study concludes by a) discussing the empirical case in relation to Schön's 'Educating the Reflective Practitioner' and b) outlining some implications for educational practice.